Perilaku Konsumtif Pengguna Klinik Kecantikan Dan Perawatan Tubuh Di Kota Pekanbaru - Situmorang, Dhuni Arta; Asriwandari, Hesti (Peneliti.net, 2025)
Pekanbaru as a metropolitan city is developing very rapidly in the modernization era and has become a role model for districts or cities on various sides of its development. The shift in urban lifestyles in interpreting beauty is evidenced by the mushrooming of Pratama beauty clinics in the city of Pekanbaru. Women from various backgrounds and ages have different meanings and standards of beauty, so their lifestyles encourage consumer behavior towards various facial and body treatments provided by beauty clinics. Therefore, this research was carried out with the aim of finding out the consumer lifestyle and the meaning of beauty for beauty clinic users in the city of Pekanbaru. The method used in this research is descriptive qualitative with lifestyle theory by David Chaney, consumer behavior theory and hyperreality by Baudrillard. The informants in this research included beauty clinic customers, clinic staff and doctors. The results of this research are facial and body beauty care as a consumptive lifestyle for women in interpreting and meeting beauty standards. Women's consumptive lifestyle towards using treatments at beauty clinics also shows their social status or image in their environment. The hyper-reality that occurs is that women undergo treatment at beauty clinics because they feel it is safer to be handled directly by a specialist doctor, so their safety is more guaranteed and they are guaranteed to get the desired results more quickly and instantly. However, beauty treatments also have a dependency effect, making consumer behavior unavoidable because women's need for appearance has become a primary need.